Stability Indicating Analytical HPLC Method Development and Validation for the Simultaneous Quantification of Tobramycin and Fluorometholone in Ophthalmic Suspension (Journal of Pharmaceutical Negative Results, 2023)
The combination of tobramycin and fluorometholone was available as eye drop formulation used to treat various bacterial infections of eye like conjunctivitis or pink eye. In literature, there is no stability indicating HPLC method reported for the quantification of tobramycin and fluorometholone. Hence the present study was aimed to establish a simple and sensitive HPLC method for the quantification of tobramycin and fluorometholone in eye drop formulations. The separation of analytes was achieved on spherisorb ODS1 (Waters) C18 (250×4.6 mm; 5 µ id) as stationary phase, acetonitrile: methanol: 0.1% orthophosphoric acid in 45:53:02 (v/v) at pH 4.4 as mobile phase at 0.8 mL/min flow rate. The analytes that were separated in column were detected using UV detector at 219 nm. In this condition, well resolved, retained peaks were identified at 3.4 min for tobramycin and 7.8 min for fluorometholone. The method reports 0.227 µg/mL and 0.076 µg/mL for tobramycin and fluorometholone respectively as LOD that proves that the method have enough sensitivity levels for the detection analytes in samples. The method passes all the validation parameters as per the guidelines proved that the method was valid. The method can shows very less % degradation in various stress studies such as acidic, base, peroxide, thermal and UV light conditions and can effectively separate various stress degradation compounds and confirms the stability indicating nature of the method. The method applicability was assessed by analysing the drug content in eye drops with a % assay of 99.01 % and 98.79 % respectively for tobramycin and fluorometholone. Based on the results, it can be concluded that the method can adequately suitable for the separation and quantification of tobramycin and fluorometholone hence can be applicable for the routine analysis of tobramycin and fluorometholone in eye drops formulations.